Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was working on the proof of dominated convergence theorem, and in the proof, I saw the following argument:

By Fatou's lemma, $$\int g + \int f \leq \lim \inf \int (g + f_n) = \int g + \lim \inf \int f_n$$ and $$ \int g - \int f \leq \lim \inf \int (g - f_n) = \int g - \lim \sup \int f_n$$

So you can see that, in the second equation (in the equality part), we converted liminf to limsup. I did not understand the whole transition here, I would be very happy if anyone helps. Thanks.

share|cite|improve this question
Because $$\liminf \left(-\int f_n\right)=-\limsup\int f_n$$ – leo Nov 8 '12 at 4:46
up vote 1 down vote accepted

First note that if $b_n$ is a sequence then $$\liminf_n (-b_n) = - \limsup_n b_n$$ The proof for this is relatively straight forward. $$\liminf_n (-b_n) = \lim_n \inf_{k \geq n} (-b_k) = \lim_n (-\sup_{k \geq n} (b_k)) = - \lim_n (\sup_{k \geq n} (b_k)) = - \limsup_n b_n$$ Now lets define $h_n^{(1)}(x) = g(x) + f_n(x)$ and $h_n^{(2)}(x) = g(x) - f_n(x)$.

The first assumption in LDCT is $\vert f_n(x) \vert \leq g(x)$. This implies that $h_n^{(1)}(x)$ and $h_n^{(2)}(x)$ are both non-negative over the underlying domain. Hence, by Fatou's lemma, we have that $$\int \liminf h_n^{(1)} d \mu \leq \liminf \int h_n^{(1)} d \mu$$ and $$\int \liminf h_n^{(2)} d \mu \leq \liminf \int h_n^{(2)} d \mu$$ Hence, we have that $$\int g d \mu + \int \liminf f_n d \mu \leq \int g d \mu + \liminf\int f_n d \mu$$ and $$\int g d \mu + \int \liminf (-f_n) d \mu \leq \int g d \mu + \liminf\int (-f_n) d \mu$$ The next assumption in LDCT is $\int g d \mu < \infty$. Hence, we can cancel $\int g d \mu$ from both equations to get $$\int \liminf f_n d \mu \leq \liminf\int f_n d \mu$$ and $$\int \liminf (-f_n) d \mu \leq \liminf\int (-f_n) d \mu$$ Now since $$\liminf_n (-b_n) = - \limsup_n b_n$$ the second equation can be written as $$\int -\limsup (f_n) d \mu \leq -\limsup\int f_n d \mu$$ which can be rewritten as $$\int \limsup (f_n) d \mu \geq \limsup\int f_n d \mu$$ The last assumption in LDCT is that $f_n \to f$. Hence, we have that $\limsup (f_n) = f = \liminf (f_n)$. Hence, we get that $$\limsup\int f_n d \mu \leq \int f d \mu \leq \liminf\int f_n d \mu$$ But we know that for any sequence $\{a_n\}$, $$\liminf_n a_n \leq \limsup_n a_n$$ and equality holds only when limit exists. Hence, putting all this together, you get that $$\lim_n \int f_n d \mu = \int f d \mu$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.